The Effect of Giving Palm Sap (Borassus Flabellifer Linnaeus) on Hydration Status After Aerobic Exercise - Muhamad Zakiudin; Heri Purnama Pribadi (Journal of Strength and Conditioning, 2026)
Dehydration is a common physiological condition that occurs after physical activity, particularly aerobic exercise, due to increased core body temperature and fluid loss through sweat. Unreplaced fluid and electrolyte loss can disrupt the body's fluid balance and impair performance and recovery. Mineral water is often used as a rehydration fluid, but it does not contain the optimal amount of carbohydrates and electrolytes to support fluid absorption. Palm sap water (Borassus flabellifer L.) has the potential to be a natural rehydration alternative because it contains simple carbohydrates and electrolytes. This study aimed to analyze the effect of palm sap water on hydration status after aerobic exercise compared to mineral water. This study used a quasi-experimental design with a randomized pretest-posttest control group design. Thirty healthy male university students aged 18–20 years were divided into two groups: the palm sap water group and the mineral water group. All subjects performed aerobic exercise, consisting of running for 30 minutes at an intensity of 64–76% of HRmax. After the activity, each group was given 250 mL of fluid according to the treatment. Hydration status was measured using Bioelectrical Impedance Analysis (BIA) with Total Body Water (TBW) as the parameter before and after the intervention. Data analysis used paired sample t-tests and independent sample t-tests. The results showed an increase in TBW values ​​in both groups, but this was not statistically significant (p>0.05). Furthermore, there was no significant difference between the palm sap water and mineral water groups in the post-test (p>0.05). This indicates that both fluids are equally effective in maintaining body fluid balance during moderate-intensity aerobic activity.Insert short English abstract here. The abstract should be in Cambri font style, 9 font size, and justified. It should not exceed 300 words. You can write your article’s abstract using this style and replacing with this information text.